Short chain: A solution for current capitalization of vegetable production - Ancuţa Marin (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
Vegetables market is one of the most important sectors of the global economy is an area characterized by multiple contradictions. According to contract concluded with MARD ICEADR runs from 2015- 2018, ADER project 16.1.2 - "Models of development of short chains for the capitalization of vegetable production on primary production- services - storage - processing - sales market." Project falls under the the objectives of Sectorial Program ADER on mechanization and automation of processes in agriculture and development of conditioning systems - storage -processing of Romanian agricultural products. Among the project objectives are included: stimulating farmers to association / cooperation presenting them the opportunities by organizing a survey among the most important vegetable growing counties. The purpose of this paper is to identify the problems faced by small and medium producers of vegetable and highlighting their opinions to formulate proposals for the effective realization of vegetable production.
Keywords: 330; short chain; vegetable growers; production of vegetables; subsidies